A Book in four Languages : English - Spanish - French - Mandarin My Emotions - Winslow, Claire; Dresen, Kris; Jiang, Muyun; Luc, Elisabeth; de Alba, Arlette (Chicago, USA Sunbird Books, 2021)
Make colorful faces as you learn words fo 10 feelings!
Linguistic Notions
Keywords: Language and Languages